2016
DOI: 10.1101/gr.206060.116
|View full text |Cite
|
Sign up to set email alerts
|

A GC-rich sequence feature in the 3′ UTR directs UPF1-dependent mRNA decay in mammalian cells

Abstract: Up-frameshift protein 1 (UPF1) is an ATP-dependent RNA helicase that has essential roles in RNA surveillance and in posttranscriptional gene regulation by promoting the degradation of mRNAs. Previous studies revealed that UPF1 is associated with the 3 ′ untranslated region (UTR) of target mRNAs via as-yet-unknown sequence features. Herein, we aimed to identify characteristic sequence features of UPF1 targets. We identified 246 UPF1 targets by measuring RNA stabilization upon UPF1 depletion and by identifying m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 48 publications
7
81
0
Order By: Relevance
“…Earlier studies demonstrated that UPF1 targets transcripts with GC-rich 3= UTRs (9,10), and both U1D and p26 were identified as preferentially protected transcripts with GC-rich 3= UTRs in the present study ( Fig. 5B).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Earlier studies demonstrated that UPF1 targets transcripts with GC-rich 3= UTRs (9,10), and both U1D and p26 were identified as preferentially protected transcripts with GC-rich 3= UTRs in the present study ( Fig. 5B).…”
Section: Discussionsupporting
confidence: 76%
“…EJC-independent NMD occurs when UPF1 bound to the 3= untranslated region (UTR) interacts with eukaryotic release factor 3 (eRF3), which is associated with a terminating ribosome, leading to phosphorylation of UPF1 (2). While UPF1 can bind to any accessible RNA, binding is enriched in transcripts that are GC rich (Ͼ15% increased GC content compared to average) (9,10), as well as in transcripts with long 3= UTRs (Ͼ1.5-fold-greater length than average) (11,12).…”
mentioning
confidence: 99%
“…It is tempting to propose rather that, by unwinding GC-rich double-stranded regions over the entire length of the mRNA, DDX6 facilitates XRN1 progression. UPF1, another RNA helicase involved in mRNA decay, has also been shown to preferentially affect the decay of GC-rich mRNAs [49]. The same observation was made for targets of the NMD pathway, which involves UPF1, SMG6 and SMG7 [50].…”
Section: Distinct Decay Pathwaysmentioning
confidence: 66%
“…BRIC-seq enables the determination of genome-wide RNA stability by monitoring the decrease in BrU-labeled RNA abundance over time from which the RNA half-life of each transcript is calculated. By comparing the half-lives of transcripts in control cells with the halflives of those in PUM-depleted cells, we can identify mRNAs of which stability is regulated by PUMs 11 . Combining the results of the RIP-seq and BRIC-seq analyses yields the targets of PUMs ( Figure 1A).…”
Section: Identification Of Target Mrnas Of Human Pum1 and Pum2 By Ripmentioning
confidence: 99%
“…For the RBPs involved in mRNA decay, not all mRNAs that bind the RBP are targets of degradation. For instance, only subset of the mRNAs that bind to UPF1, an RBP involved in the RNA degradation and RNA quality control, is subject to UPF1-dependent mRNA degradation 11 . Consequently, knowledge of the mRNAs that bind an RBP is insufficient.…”
Section: Introductionmentioning
confidence: 99%